Morphological and Phenological Characterization of Some Potato Cultivars in Turkey - Yusufoğlu, İbrahim; Akıncı, Sermin; Hajhamed, Abdulsalam (Journal of agricultural, environmental and veterinary sciences, 2021)
Fifteen potato cultivars were morphologically and phenologically characterized under greenhouse conditions in 2019 and 2020. The highest percentage of emergence was 100% in L-Olympia and the lowest was 12.5% in Malice within the first 25 days after planting (DAP). The duration to complete 100% emergence was 7.33 days in Soleia as the shortest period, meanwhile, it was 15.67 days in Triomphe. The stems number ranged between 2.13 in both Passion & Aurea and 7.50 in L.Olympia. The highest plant was 14.71, 35.83 at 25, 35, respectively in L-Olympia and 80.33 cm in Blondine at 45 DAP. The lowest height was 3.21, 9.13 and 46.17 cm at 25, 35, and 45 DAP, respectively in Malice. Only nine cultivars were able to give inflorescences. The highest number of inflorescences was 5.00 in Toronto and the highest number of flowers per inflorescences was 15.00 in Aurea. The flowering duration ranged between 14.33 and 43.20 days in Blondine and Triomphe, respectively. Many correlation coefficient relationships were noted between traits, a significantly positive correlations coefficient between stems number and plant height, stems numbers and tubers number per plant, plant height and tubers number per plant. Meanwhile, significantly negative correlation coefficient was noted between number of stems per plant and average of tuber weight, duration of emergence and plant productivity. Overall results of this study suggest there is a big differences among potato genotypes led to farther morphological and phenological traits can be improved for having most suitable and adaptable potato cultivars in Turkey.
Keywords: potato cultivars; Solanum tuberosum; Morphology; Phenology; Flowering; Emergence; Turkey